A Rare Tumor Mimicking Bronchial Asthma - Mishra, Navin Kumar; Thakuri, HemaChand; Shrestha, Sareen; Khadka, Gaurav; Sha, Parmeshwar; Dhamala, Rasmita; Rai, Utshav (Nepalese Respiratory Journal, 2025)
Wheezing is a common symptom that leads us to assume most cases are obstructive airway disease. We present a case of a 45-year-old female without any comorbidities who presented with recurrent episodes of wheezing and was treated at multiple centers with escalating doses of inhaled corticosteroids and bronchodilators. She was then diagnosed with adenoid cystic carcinoma when she developed post-obstructive pneumonia and presented to our center. She underwent complete resection with no residual disease and no further requirement for any inhalers.